ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT SABUN MANDI BIASA DI KOTA YOGYAKARTA - -, Ibrahim -; Suman, Agus -; Salim, Ubud - (Program Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT Â The study has as its rationale the fact that there are numerous brands of bath soap in the market. The changes of consumer behavior, which influenced by the economy crisis occurred in Indonesia, has suppressed the producers to readjust their marketing programs. It is crucial for the firms to recognizeÂ the consumer attitudes on their products in making their marketing programs. The study was aimed at understanding: (1) the consumer attitudes on the bath soapsâ (i.e., Lux and Giv brands) attributes, (2) the influence of the consumerâs social environment toward the subjective norm in making the purchasing decision on the Lux and Giv, (3) the differential of consumers attitudes on the Lux and Giv. Interview and questionnaire were used to collect data, by using the semantic differential scale method. Fishbein model and Wilcoxonâs signed rank test were applied to test the studyâs results. Results of the study showed that: (1) there was a positive attitude of consumer on both the Lux and Giv. âAromaâ, whereas âprestigeâ had the lowest positive score for the Giv; (2) the consumerâs social environment influenced the subjective norms of consumer in making the purchasing decision of the Lux and Giv. âFamily membersâ was the dominant variable of both the Lux and Giv; (3) there were the differences in the consumer attitude between the Lux and Giv brands. By the differential test for each attribute, then, it was showed that there were the significant differences in the consumer attitude on the productâs attributes,Â except for the âpackagingâ. Based on the study results and empirical evidences supported by the statistical testing,Â it is showed that the two bath soap brands have dominate the consumerâs mind. Nevertheless, in making their purchasing decision, the consumers have the difference attitudes in assesing those two brands depends on their desires. Keywords : consumer behavior, bath soap attributes